Antecedents of Use of e-SPT and Their Impact on Taxpayer Compliance (Case Study: Special Region of Yogyakarta) - Juwita Andriani (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2021)
The development of information technology today is very helpful for all human activities such as ordering goods, buying and selling, applying for jobs, and so forth. Modernization of tax administration is carried out by the DJP as a form of improving the quality of taxation services to taxpayers, one of which is the development of debt tax reporting using electronic SPT (e-SPT) or by using computers. The population in this study is taxpayers who live in the Special Region of Yogyakarta. The sample in this study is individual taxpayers who live in the Special Region of Yogyakarta. This study uses a purposive sampling technique with criteria for taxpayers who have NPWP and taxpayers who use e-SPT. The type of data used in this study is primary data obtained by researchers directly or sent via Google form. The results of this study prove that the perceived usefullnes does not affect the use of e-SPT. Perceived easy of use has a positive effect on the use of e-SPT. Security and privacy have a positive effect on the use of e-SPT. The use of e-SPT has a positive effect on tax compliance. Test equipment used in this study was SEM-PLS with 158 respondents.